Asymmetries in/of Translation: Translating Translated Hispanicism(s) - Ruano, Rosario; Vidal Claramonte, Carmen (TTR : traduction, terminologie, rédaction, 2004)
AbstractThis paper focuses on the hybrid writing of American authors of Hispanic descent in its double dimension as a process of translation and representation, and also as a process subject to other processes of translation and representation, including scholarly assessment and description. It examines the problems and ideological implications of translating these translated fictions, inasmuch as this writing calls into question both traditional visions of literature and hegemonic translation models.